Mineralizing Filamentous Bacteria from the Prony Bay Hydrothermal Field Give New Insights into the Functioning of Serpentinization-Based Subseafloor Ecosystems - Pisapia, Céline; Gérard, Emmanuelle; Gérard, Martine; Lecourt, Léna; Lang, Susan Q.; Pelletier, Bernard; Payri, Claude E.; Monnin, Christophe; Guentas, Linda; Postec, Anne; Quéméneur, Marianne; Erauso, Gaël; et al. (Frontiers in Microbiology, 2017)
Despite their potential importance as analogs of primitive microbial metabolisms, the knowledge of the structure and functioning of the deep ecosystems associated with serpentinizing environments is hampered by the lack of accessibility to relevant systems. These hyperalkaline environments are depleted in dissolved inorganic carbon (DIC) making the carbon sources and assimilation pathways in the associated ecosystems highly enigmatic. The Prony Bay Hydrothermal Field (PHF) is an active serpentinization site where, similar to Lost City (Mid-Atlantic Ridge), high pH fluids rich in H2 and CH4 are discharged from carbonated chimneys at the seafloor, but in a lagoonal environment. This study aimed at characterizing the subsurface microbial ecology of this environment by focusing on the earliest stages of chimney construction, dominated by the discharge of hydrothermal fluids of subseafloor origin. By jointly examining, at the micrometric scale, the mineralogy and the microbial diversity of the conduits of juvenile edifices, we find a central role of uncultivated bacteria belonging to the Firmicutes in the ecology of the PHF. These bacteria, along with members of the phyla Acetothermia and Omnitrophica, are identified as the first chimneys inhabitants before archaeal Methanosarcinales. They are involved in the construction and early consolidation of the carbonated structures via organomineralization processes. Their predominance in the most juvenile and nascent hydrothermal chimneys, and their affiliation with environmental subsurface microorganisms, indicate that they are likely discharged with hydrothermal fluids from the subseafloor. They may then be representative of endolithic serpentinization-based ecosystems, in an environment where DIC is limited. In contrast, organic compounds coming from abiotic by-products of serpentinization processes and/or from deep life activity could constitute valuable sources of carbon in these environments where Firmicutes are largely represented, as well as heterotrophic and fermentative microorganisms. We thus propose that the Firmicutes retrieved at PHF may have a versatile metabolism with the capability to use diverse organic compounds from biological or abiotic origin. From that perspective, this study shed new light on the structure of deep microbial communities living at the energetic edge in serpentinites and may provide an alternative model of the earliest metabolisms.